Pengembangan lembar kerja siswa Sekolah Dasar berbasis etnomatematika dengan setting Candi Borobudur - Edi Riyanto; Teguh Wibowo; Riawan Yudi Purwoko; Wharyanti Ika Purwaningsih (Universitas Muhammadiyah Purworejo, 2020)
The background of this research is come from the fact which is not available in teaching material according to background from students culture in Indonesia. Therefore, the result of this research is to produce a product students Mathematics worksheet which is combination the material and culture value especially Borobudur temple. The aims of the research is to find out validation of product LKS elementary school based ethnomatematics with the setting of Borobudur temple on two-dimentional figure theory. The development model is used in this research is ADDIE (Analysis, Design, Development, Implementation and Evalaluation). This research has produced a student worksheet which is integration ethnomatematics of Borobudur Temple in a two-dimentional figure theory that is valid. The criteria of validity is find out from 6 validator assesments, these are 2 media experts with an average of 3.3, 2 theory experts with an average of 3.4, and 2 learning experts with a score of 3.5. The average of the overall ratings is 3.4 categorized valid. Based on these results, LKS which is developed categorized valid.